How does the physiological activity and growth of tomato plants react to the use of a soil-mineral compound? - Pereira, Isabella Sabrina; Fagan, Evandro Binotto; Cabral, Ellen Mayara Alves; Fontana, Daniele Cristina; Umburanas, Renan Caldas; Soares, Luís Henrique (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
The tomato crop has a high productive potential that can be depleted by biotic and abiotic stresses. Increased plant resilience to stress conditions has been reported with foliar applications of soil-mineral compounds; however, it is necessary to better understand how plants react to the use of this compound. Thus, this study evaluated the effect of foliar applications of a soil-mineral compound on the physiological and growth attributes of tomato plants. This experiment was carried out in Lagoa Formosa/MG during 2016. Different rates of the soil-mineral compound were used during the crop cycle, forming four distinct managements. The management consisted of different doses of the mineral compound in four stages after transplanting the tomato seedlings. The experiment design used randomized blocks. The following physiological evaluations were performed: total soluble protein, hydrogen peroxide, nitrate reductase enzyme activity, urease, superoxide dismutase (SOD), peroxidase, phenylalanine ammonia lyase, and lipid peroxidation (LP). The growth assessments were plant biomass and yield. Foliar applications of the soil-mineral compound increased the activity of the SOD enzyme by 4.17 and 6.25%. The use of the soil-mineral compound also increased the LP activity and reduced the antioxidant enzyme activity. The foliar application of the soil-mineral compost at doses of 0.5, 0.750, 1.0 and 1.0 kg ha-1 at 15, 25, 40 and 60 days after transplanting, respectively, increased the yield of the table tomatoes by 20%.